Faktor-Faktor yang Mempengaruhi Kepatuhan Masyarakat dalam Program Jaminan Kesehatan Nasional (JKN) Di Indonesia : Literature Review - Kania Rizqita Dewi; Putri Regita Miolda; Triayu Nur Afifah; Novita Dwi Istanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The JKN Program is an effort to equalize the quality of health services for all Indonesians, with a wide range of health services and affordable contributions. The JKN program has many benefits, but there are still many participants who do not comply with the JKN program rules, for example, do not pay contributions on time. This study aims to determine the factors that can influence public compliance with the JKN program in each region of Indonesia. The method in this study uses a literature review design by collecting research sources in the form of valid articles. After several article sources have been collected, the researcher reviews the published article sources to produce a new analysis. Based on the results of the study, it can be concluded that the factors that influence the compliance of JKN participants in paying contributions are the level of knowledge, income level, and perceptions of health risks that are owned by each member of the community. The use of first-level health facilities can also affect participant compliance in seeking health services and social, economic, and cultural presence are also a number of external factors in JKN participant compliance.